2015
DOI: 10.5505/tjb.2015.32448
|View full text |Cite
|
Sign up to set email alerts
|

Comparation of Heavy Metals and Selenium Contents in The Digestive Gland and Gills of Mytilus galloprovincialis (Lamarck, 1819) Caught in Izmir Bay (Turkey)

Abstract: Comparative study of heavy metals and selenium accumulation in the digestive gland and gills of Mytilus galloprovincialis (Lamarck, 1819) caught in Izmir bay (Turkey) [İzmir Körfezi'nden (Türkiye) yakalanan Mytilus galloprovincialis (Lamarck, 1819)'un sindirim bezi ve solungaçlarındaki ağır metal ve selenyum içeriklerinin karşılaştırması] ABSTRACTObjective: The aim of this study was to evaluate heavy metals (Cr, Fe, Ni, Cu, Zn, As, Cd, Hg, Pb) and selenium levels in digestive gland and gill tissues of wild Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The heavy meal concentration in the tested samples were in the following order: As > Pb > Cd > Hg. The study by Yabanli et al 20 has also found the presence of heavy metals in the tissue of mussels, with the reported values (mg kg −1 of dry weight) as follows: 0.17 and 0.15 for Cr, 28.62 and 29.49 for Fe, 0.25 and 0.29 for Ni, 2.53 and 1.78 for Cu, 18.52 and 22.03 for Zn, 1.26 and 1.08 for As, 0.04 and 0.04 for Cd, 0.02 and 0.02 for Hg, 0.19 and 0.16 for Pb, 0.40 and 0.48 for Se. In addition, it has been proven that the presence of heavy metals can cause proteosome-mediated protein degradation in crab ( Cancer paragus ) but the effect was smaller compared to other species of crustaceans such as lobsters 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The heavy meal concentration in the tested samples were in the following order: As > Pb > Cd > Hg. The study by Yabanli et al 20 has also found the presence of heavy metals in the tissue of mussels, with the reported values (mg kg −1 of dry weight) as follows: 0.17 and 0.15 for Cr, 28.62 and 29.49 for Fe, 0.25 and 0.29 for Ni, 2.53 and 1.78 for Cu, 18.52 and 22.03 for Zn, 1.26 and 1.08 for As, 0.04 and 0.04 for Cd, 0.02 and 0.02 for Hg, 0.19 and 0.16 for Pb, 0.40 and 0.48 for Se. In addition, it has been proven that the presence of heavy metals can cause proteosome-mediated protein degradation in crab ( Cancer paragus ) but the effect was smaller compared to other species of crustaceans such as lobsters 21 .…”
Section: Introductionmentioning
confidence: 99%